(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Three new and a known species of Prismatolaimus de Man, 1880 are described and illustrated. Prismatolaimus lacustris sp. n. and P. amphidialis sp. n. are monovarial species without males in the population. P. lacustris sp. n. (L= 0.68- 0.80, a= 35.1-47.1, b= 3.7-4.2, c= 3.6-3.9) is characterised by having single-jointed outer labial setae; large stoma with prominent dorsal tooth and denticulate ridges; relatively posterior amphids; moderately long post-uterine sac; vagina with refractive pieces; and long, ventrad curved tail with a minute dorsal mucro. P. amphidialis sp. n. (L= 0.58-0.68, a= 37-44, b= 4.0-5.4, c= 3.9-4.3) is characterised by its short stoma with inconspicuous stegostom, almost indiscernible dorsal tooth and absence of denticulate ridges; prominent sensillar pouches of amphids; small post-uterine sac; and long filiform tail ventrad curved, with undemarcated mucro. P. macrostomus sp. n. (L= 1.02-1.21, a= 51.2-55.0, b= 4.6-5.2, c= 3.2-3.3) is characterised by being large-sized, diovarial females having sparse 4-5 ƒÊm long somatic setae; long, double articulated labial setae; large barrelshaped stoma with a massive dorsal tooth and rows of inconspicuous subventral denticles; pre-equatorial vulva; and long filiform tail with a pointed dorsal hook. P. andrassyi Khera & Chaturvedi, 1977 has been redescribed with morphometrics of populations from four localities.